Shifting Spectra: Comparative Approaches to Image Making in Science and Art University of the Arts London. Central Saint Martins. - Kesseler, Rob (Revelar: Revista de Estudos da Fotografia e Imagem, 2024)
Shifting spectra sits upon an evolving history of image making in relation to science as it has evolved from conventional graphic means, through early photography into a complex digital domain. The paper goes on to explore a territory in which the artist and the scientist generate comparative images of complex micro-organisms. Their results converge and diverge as defined by the parameters and potential of the technology, the intended audience, and their personal aesthetic. The past twenty years have seen extensive advances in micro imaging that enable the scientist to move beyond the limitations of earlier protocols and this is a territory into which artists have increasingly been drawn. This article reflects on the history of photography and science and draws upon recent collaborations between the author and botanical scientists working in the United Kingdom, Germany and Portugal in which microscopy fulfils the dual role of scientific analysis and artistic interpretation of plant science